(untitled) (Indian Journal of Public Health Research & Development, 2020)
Context: Modern studies have shown that one of the risk factors for recurrent thrombosis, coronary heart disease and cerebrovascular pathology is the level of homocysteine in the blood. An analysis was made of the severity of homocysteinemia in patients with coronary heart disease with episodes of painless myocardial ischemia, and it was corrected with B vitamins. 84 patients with coronary heart disease with functional angina pectoris I-III were examined. It was found that the combination of hyperhomocysteinemia and frequent episodes of painless myocardial ischemia is recorded mainly in patients with a high functional class of angina pectoris. Reception of B vitamins can significantly reduce the concentration of homocysteine in blood plasma and the frequency of episodes of painless myocardial ischemia.